Diplomasi Maritim Indonesia dalam Kasus Illegal Fishing oleh Nelayan Vietnam Tahun 2018-2019 - Anggraini Ika Sasmita (Universitas Airlangga, 2021)
Indonesia is considered as a maritime state due to the fact the 2/3 of its territory is covered by the sea. Indonesian waters hold a high potential for maritime resources. With this potential comes a challenge for Indonesia to manage and protect its maritime resources from foreign actors that try to enter Indonesian waters and exploit the resources in it illegally or conduct illegal fishing. Vietnam has become the country of origin for most of the perpetuators of illegal fishing from 2018-2019. This research aims to explain the efforts of Indonesia through maritime diplomacy to in order to tackle the issue of illegal fishing that has been conducted by Vietnamese fishing ships. This article will use the UNCLOS 1982 convention as a legal basis and the concepts of maritime security and maritime diplomacy as a theoretical basis to explain Indonesia’s maritime borders and efforts to assert sovereignty over Indonesian maritime territory. A descriptive research method will be used in this article. This article views that Indonesia’s maritime diplomacy effort is still in compliance with UNCLOS 1982 and the theory of maritime diplomacy which includes the following: 1) cooperative diplomacy which is conducted through bilateral cooperation; 2) persuasive diplomacy through displaying presence in maritime territory; 3) coercive diplomacy through sinking of Vietnamese fishing ships.